Pemanfaatan Tanaman Gulma Berbunga sebagai Mikrohabitat Musuh Alami Pada Tanaman Kedelai di Lahan Sub Optimal - Lisdayani, Lisdayani; Susanti, Rini (UNIVERSITAS LABUHANBATU, 2023)
Weeds have strong competitive abilities for CO2, water, sunlight and nutrients. Weeds have a direct effect on the growth and yield of soybean plants. Refugia is an area of weeds that is not disturbing because of its role as a microhabitat that provides shelter spatially and/or temporally for natural enemies of pests, such as predators and parasitoids, as well as supporting components of biotic interactions in ecosystems, such as pollinators or pollinating insects. This research was conducted in a village district level of deli serdang district, using factorial randomized block design (RBD). The results showed that the natural enemies found in soybean plants were mostly from the predator class, and the content of secondary metabolites was known to be saponins and flavanoid compounds, which are compounds found in T.erecta weeds.Keywords: Soybean, Flowering Weeds, Natural Enemies